Deflection distribution estimation of the main arch of arch bridges based on long-gauge fiber optic sensing technology. Issue 15 (November 2019) - Zhang, Qingqing; Sun, Tongfei; Wang, Jing; Liu, Qianlong
Deflection of the main arch of arch bridges is one of the main indices for supporting the alignment after construction and evaluating the structural performance. The existing sensing technology and analysis method for deflection monitoring have developed, but it is still difficult to monitor the deflection of the main arch of a long-span arch bridge with great height difference between measuring points. On the contrary, in recent years, with the outstanding advantages of fiber optic sensing technologies, a long-gauge fiber Bragg grating sensing technology has been used in structural health monitoring due to its characteristics, including reflecting the macro and micro information and being connected into network. For these reasons, the long-gauge fiber Bragg grating sensing technology is proposed to develop a method to monitor the deflection of the main arch of arch bridges. A curvature load method for deflection distribution estimation using strain measurements is proposed. It deduces the expression of the complex relation between the strain and the deformation on the main arch element and then separates the coupled strain on the element through the specific sensor layout. A series of simulation tests of the deck arch bridge, half-through bridge, and through arch bridge was conducted. It is concluded that the proposed method can not only be applied to these long-span arch bridges but also can identify the static and dynamic deflections of the main arch effectively.